Cybersecurity : protecting critical infrastructures from cyber attack and cyber warfare - Johnson, Thomas A. (Boca Raton : CRC Press/Taylor & Francis Group, 2015)
The World Economic Forum regards the threat of cyber attack as one of the top five global risks confronting nations of the world today. Cyber attacks are increasingly targeting the core functions of the economies in nations throughout the world. The threat to attack critical infrastructures, disrupt critical services, and induce a wide range of damage is becoming more difficult to defend against. Cybersecurity: Protecting Critical Infrastructures from Cyber Attack and Cyber Warfare examines the current cyber threat landscape and discusses the strategies being used by governments and corporations.
Historical reference points in the computer industry and emerging challenges in cybersecurity / Thomas A. Johnson -- Critical infrastructures, key assets : a target-rich environment / Thomas A. Johnson -- Protection and engineering design issues in critical infrastructures / Fred Cohen -- Cyber intelligence, cyber conflicts, and cyber warfare / Thoams A. Johnson -- Cybersecurity : a primer of U.S. and international legal aspects / Julie Lowrie -- Economic cost of cybersecurity / Thomas A. Johnson -- Cybersecurity Threat landscape and future trends / Thomas A. Johnson.
Includes bibliographical references and index.
Keywords: Computer security